2017
DOI: 10.1002/ptr.5766
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Metastatic Effect of Dehydrocorydaline on H1299 Non-Small Cell Lung Carcinoma Cells via Inhibition of Matrix Metalloproteinases and B Cell Lymphoma 2

Abstract: Though Dehydrocorydaline, an alkaloid isolated from Corydalis turtschaninovii tuber, was known to have anti-coronary artery disease, anti-inflammatory, apoptotic, anti-allergic, anti-acetylcholinesterase, and antitumor effects, the underlying anti-metastatic mechanism of Dehydrocorydalin was never elucidated in lung cancer cells so far. Thus, in the present study, the anti-metastatic effect of Dehydrocorydaline was examined in non-small cell lung carcinoma (NSCLC) cells, mainly targeting matrix metalloproteina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…Several natural products from Corydalis yanhusuo W.T. Wang have been demonstrated to have extensive pharmacological activities [28,29]. In this report, our results indicated that perisciatic nerve administration of l-CDL (1.5, 3, and 6 mg/kg) on the operated side of CCI rats also attenuated CCI-induced neuropathic pain in a dose-dependent manner and without tolerance.…”
Section: Discussionsupporting
confidence: 55%
“…Several natural products from Corydalis yanhusuo W.T. Wang have been demonstrated to have extensive pharmacological activities [28,29]. In this report, our results indicated that perisciatic nerve administration of l-CDL (1.5, 3, and 6 mg/kg) on the operated side of CCI rats also attenuated CCI-induced neuropathic pain in a dose-dependent manner and without tolerance.…”
Section: Discussionsupporting
confidence: 55%
“…Dehydrocorydaline (compound 7 ), an alkaloidal component, has been recently reported to exert analgesic [ 30 ], anti-inflammatory [ 31 ], and antitumor effects [ 32 ]. Also, it has been found to act on opioid receptors [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of small new molecules targeting MMPs have been engineered and studied for their potential application in arthritis treatment. These include plant derivatives such as dehydrocorydaline, shown to inhibit both mRNA and protein levels of MMP7 and MMP9 [73], and caffeic acid, which inhibits MMP9 activity [74,75]. Moreover, using a computational/directed-evolution approach to protein engineering, Arkadash et al engineered an N-TIMP2 mutant that is able to selectively inhibit MMP14, overcoming the main limitation of MMP inhibitors, i.e., numerous, serious side effects due to their broad, non-selective inhibitory effect on MMPs [76].…”
Section: Therapeutic Implications Of Targeting Matrix Metalloprotementioning
confidence: 99%